Actant affordances: a brief history of affordance theory and a Latourian extension for education technology research - Blewett, Craig (Critical Studies in Teaching and Learning, 2023)
Affordance theory provides a useful lens to explore the action opportunities that arise between users and technology, especially in education. However developments in the theory have resulted both in confusion and misapplication, due partly to issues related to affordance theory’s ontology. This paper outlines two competing perspectives on affordances by Gibson and Norman, before arguing that Latour’s theory of ‘actants’ provides a useful middle way between these competing positions. This ‘actant affordance’ provides new opportunities for undertaking educational technology research that focuses on the network of negotiations taking place between actants (student, teacher, technology, pedagogy, etc.) rather than studying causality or simple binaries.